IMPROVING PEDAGOGICAL COMPETENCE BY IMPLEMENTING MICROTEACHING IN ISLAMIC RELIGIOUS EDUCATION PRODUCTS - Ajat Saputra; Santi Ristiana, Santi Solihat, Silma Mausuli (Adisam Publisher, 2024)
This study aims to describe: Efforts to improve pedagogical competence by conducting microteaching PAI, (2) The Role of Microteaching Supporting Lecturers in improving pedagogical competencies of Islamic Education. This research is a descriptive qualitative research. The subjects in this study were students of islamic educatuion in 2021/2022 who had conducted microteaching in improving pedagogical competence. Data collection techniques used were in- depth interviews, observation, and documentation. The validity of the data in this study is triangulation (triangulation of sources and triangulation of techniques) and observationality. Data analysis techniques applied were data reduction, data display, and data verification. The conclusions in this study are: (1) there are various activities carried out in the implementation of microteaching as an effort to improve pedagogical competence of Islamic Education. The implementation of these activities provides increased pedagogical competence of students which includes the ability to manage learning, understanding of students, learning design, learning implementation, use of learning technology, evaluation of learning outcomes, and student development. (2) The Role of Microteaching Supporting Lecturers in improving pedagogical competencies of Islamic Education. This role includes the role of lecturers as educators, instructors, mentors, trainers, and developers in the implementation of microteacahing programs.